Photo-physical characterizations and evaluation of in-vitro antioxidant, anti-inflammatory and antidiabetic potentials of green synthesized ackee (Blighia sapida) selenium nano-particles - Omodele Ibraheem; Olubukola Helen Oyeniran; Oluwatobiloba Moses Ogundipe; Eunice Oluwabukunmi Abe; Temitope Adenike Oyedepo; Kehinde Oluseun Sodeinde; Stephen Oluwaseyi Damola; Tosin Benjamin Adeola (BMC, 2024)
Abstract Background Green synthesized nanoparticles have recently gained significant medicinal applications and oftentimes outperform their green sources. Selenium is of fundamental importance to human health, stemming from its distinctive physicochemical properties, such as antioxidant activity, inhibition of Lipid peroxidation, stabilization of membrane proteins, maintenance of membrane fluidity and modulation of cell signaling. Though reports have shown some therapeutic potential of Ackee plant parts such as antioxidant, anti-inflammatory, antimicrobial, neuroprotective, very few scientific proofs still exist in support of these effects. Methods This study synthesized selenium nanoparticles (Se-NPs) from crude methanolic extracts of Ackee leaves (AKL) and Ackee arils (AKA), examined the photo-physical characteristics of the Se-NPs and determined the in-vitro antioxidant, antidiabetic, and anti-inflammatory potentials of AKL, AKA, and their Se-NPs using established protocols. Results In both leaves and arils Se-NPs: UV spectroscopy revealed a qualitative absorbance at 310 nm; FTIR indicated multiple vibrations around 4000 cm−1- 400 cm−1; SEM images of 5 µm principally showed consistent size distribution of amorphous and granular shape at a magnification of 10,000X; while EDS spectra strongly confirm the presence of atomic Se compound at 30 kV. Various antioxidant activities assays carried out showed a range of approximately 4 to 60 times higher activities of the AKL, AKA, and Se-NPs than Ascorbic acid-the standard drug used. Furthermore, appreciable activities of more than 50% were obtained for alpha-amylase and alpha-glucosidase inhibitory activities, along with highly significant activities of haemoglobin glycosylation, glucose uptake, membrane stabilization, anti-arthritic, anti-haemolysis activities, when AKL, AKA, and Se-NPs were compared with standard drugs. Conclusion Encouraging the development and utilization of AKL, AKA, and Se-NPs will provide tremendous therapeutic efficacy and bioavailability approaches towards the management of diabetes, inflammation, and other oxidative stress-related diseases.